Fluid balance and sodium losses during indoor tennis match play - Lott, M. J. E.; Galloway, S. D. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
This study assessed fluid balance, sodium losses, and effort intensity during indoor tennis match play (17 ± 2 °C, 42% ± 9% relative humidity) over a mean match duration of 68.1 ± 12.8 min in 16 male tennis players. Ad libitum fluid intake was recorded throughout the match. Sweat loss from change in nude body mass; sweat electrolyte content from patches applied to the forearm, calf, and thigh, and back of each player; and electrolyte balance derived from sweat, urine, and daily food-intake analysis were measured. Effort intensity was assessed from on-court heart rate compared with data obtained during a maximal treadmill test. Sweat rate (M ± SD) was 1.1 ± 0.4 L/hr, and fluid-ingestion rate was 1.0 ± 0.6 L/hr (replacing 93% ± 47% of fluid lost), resulting in only a small mean loss in body mass of 0.15% ± 0.74%. Large interindividual variabilities in sweat rate (range 0.3-2.0 L/hr) and fluid intake (range 0.31-2.52 L/hr) were noted. Whole-body sweat sodium concentration was 38 ± 12 mmol/L, and total sodium losses during match play were 1.1 ± 0.4 g (range 0.5-1.8 g). Daily sodium intake was 2.8 ± 1.1 g. Indoor match play largely consisted of low-intensity exercise below ventilatory threshold (mean match heart rate was 138 ± 24 beats/min). This study shows that in moderate indoor temperature conditions players ingest sufficient fluid to replace sweat losses. However, the wide range in data obtained highlights the need for individualized fluid-replacement guidance.